Exploring the potential of Fe(III)-EGTA and Fe(III)-DTPA as the catalysts to enhance UV/persulfate in the degradation of aqueous sulfamethazine - Ng, Kuan Aeng (Water environment research : a research publication of the Water Environment Federation, 2023)
© 2023 Water Environment Federation.